DEVELOPMENT OF CONTEXTUAL-BASED STUDENT WORKSHEET ON THE THEME OF ENVIRONMENT OUR BEST FRIEND’S GRADE FIFTH ELEMENTARY SCHOOL OF SUKADANA. - Rika Triwinda; Satinem Satinem; Tio Gusti Satria (Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This development research aims to develop a Contextual-Based Student Worksheet On The Theme of Environment Our Best Friend’s Grade Fifth Elementary School Of Sukadana. The type of research is Research of Development with the Dick and Carey model. The results showed that the media validation was classified as good with a percentage of 76,85%. Linguistic validation results are categorized as good with a percentage of 71,43%. The results of the material validation category are very good with a percentage of 91,25%. Overall the result of the analysis and calculation of questionnaire scores from the expert team, Contextual-Based Student Worksheet are in the good category with a percentage of 79,84%. While the result of one-to-one are classified as good with a percentage of 73,48%. Small group trials are classified as very good a percentage of 86,75%, meaning that is Contextual-Based Student Worksheet On The Theme Of Environment Our Best Friend’s grade Fifth of Elementary School Of Sukadana valid and practical to use.